2005
DOI: 10.1002/app.22483
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of polystyrene solutions expanded with carbon dioxide

Abstract: ABSTRACT:The viscosity of solutions of polystyrene (PS) in decahydronaphthalene (DHN) was measured in the presence of carbon dioxide (CO 2 ) with a moving-piston viscometer. The effects of the CO 2 pressure (0 -21 MPa), polymer concentration (1-15 wt %), temperature (306 -423 K), and polymer molecular weight (126 and 412 kDa) on the viscosity were investigated. In the absence of CO 2 , the increase in the viscosity with increasing polymer concentration was approximately exponential in concentration and was wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…An exponential increase of the viscosity has been reported in rheological experiments on other soft colloidal systems such as emulsions 58 and polymer solutions. 59,60 It has also been predicted by Semenov et al, who showed that the relaxation time, and thus the viscosity, of a transient network of triblock copolymers should increase exponentially with concentration, in a concentration regime just above the overlap concentration. 61 This may well be the concentration regime we are investigating here.…”
Section: Rheometry Of Concentrated Solutionsmentioning
confidence: 62%
“…An exponential increase of the viscosity has been reported in rheological experiments on other soft colloidal systems such as emulsions 58 and polymer solutions. 59,60 It has also been predicted by Semenov et al, who showed that the relaxation time, and thus the viscosity, of a transient network of triblock copolymers should increase exponentially with concentration, in a concentration regime just above the overlap concentration. 61 This may well be the concentration regime we are investigating here.…”
Section: Rheometry Of Concentrated Solutionsmentioning
confidence: 62%
“…Other reported rheological measurements of CO 2 + polymer melts include poly(butylene succinate) (PBS), poly(dimethylsiloxane) (PDMS), low-density polyethylene, poly(ethylene glycol) (PEG), PMMA, polypropylene (PP), , polystyrene, , and poly(vinylidene fluoride) (PVDF) . Whittier et al report a 2 orders of magnitude reduction in the relative viscosity of PS in decahydronaphthalene in the presence of either CO 2 or SF 6 . Sarrade et al report a 5- to 500-fold reduction in the viscosities of spent oils and polymers swollen with dense CO 2 .…”
Section: 43 Transport Propertiesmentioning
confidence: 99%
“…Viscosity of PS/DHN solutions has been estimated according to Gandhi–Williams equation as a function of DHN viscosity, which has proven to be valid in a wide range of temperatures. , Viscosity of DHN solvent has been estimated with the free-volume viscosity model developed by Allal et al and the parameters given by Cain et al Estimated values of viscosity of PS/DHN mixtures at different pressures, temperatures, PS concentrations, and PS average molecular weights have been also included in Table .…”
Section: Resultsmentioning
confidence: 99%